Synthesis,Characterization and Evaluation of the Anticancer and Antimicrobial Activities of Some Novel Benzazole and Benzazine Derivatives - Shehab, Wesam Saber; Eleiwa, Naglaa Z.H.; Mouneir, Samar.M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
The present study was designed to synthesizeÂ and develop new useful lead compounds (some novel benzazole and benzazine derivatives ) of simple structure , exhibiting optimal in vitro anticancerÂ and antimicrobial potency. Phenylenediamine derivative 1 was condensedÂ withÂ dithiocarboxylic acid derivatives 2 and producedÂ Â benzimidazole derivative 4. The benzotriazepines 8 and 10Â were formed by the reaction of 1 with dicarbonyl derivatives followed by intermolecular coupling reaction. The synthesis of benzotriazine12, benzotriazole 14,17, benzimidazole16 and benzothiadiazine 19 from compound 1 was also described. The Synthesized Compounds were characterized by Spectral Studies like IR, H1 â€“ NMR and Analysis Spectra .The title compounds were screened for their possible In vitro anticancer and antimicrobial activities. Among the synthesized compounds, some have shown promisingly remarkable activities againstÂ differentÂ cancer cell lines (MCF-7 human breast cancer cells, HepG2 human hepatocarcinoma cells and PC3 human prostate cancer cells)and moderateÂ to high antibacterial and antifungal activities. The obtained results showed that the most active compounds could be useful as a template for future design, modification and investigation to produce more active analogs.